Influence of marketing in New Product Development - Danish, Tamoor (Advances in Social Sciences Research Journal, 2020)
Several marketing researchers have concluded that in many organizations the position of marketing decreases and loses its impact. If marketing plays (or should play) a substantial job inside the firm, this capability should have a noticeable voice in new product development (NPD). Keywords: Concluded, Impact, Substantial job